Activation of acetylcholine receptors on clonal mammalian BC3H-1 cells by high concentrations of agonist. - Sine, S M (1987)
1. Currents were recorded through acetylcholine (ACh) receptor channels on clonal BC3H-1 cells in the presence of high concentrations of ACh (20-1000 microM) and carbamylcholine (180-1000 microM). 2. Channel openings at high agonist concentrations occur in clusters separated by long silent periods (seconds). Clusters, in turn, show groups of closely spaced openings separated by relatively long (hundreds of milliseconds) closed periods. The closed periods between clusters and between groups within clusters are thought to reflect two desensitized states (Sakmann, Patlak & Neher, 1980). 3. Openings within groups consist largely of long-duration openings. An excess of brief-duration openings is seen at all high agonist concentrations; most brief openings occur as isolated, solitary openings. 4. The distribution of closed periods within groups shows four exponential components with time constants separated by several fold over the range of 50 microseconds to 50 ms. 5. The distribution of closed periods within groups is analysed as a function of agonist concentration, to estimate rate constants for transitions in a hypothetical reaction scheme for receptor activation. One or two of these components (depending on agonist and agonist concentration) appear to reflect agonist binding and channel gating. It is hypothesized that the other closed-period components within groups at high agonist concentrations result from additional states of doubly liganded receptors which have closed ion channels. 6. With ACh as agonist the data indicate that binding and activation saturate at concentrations above 130 microM. The data are quantitatively consistent with measurements made at low concentrations of ACh (Sine & Steinbach, 1986b), and indicate that a four-state linear scheme is able to describe major features of ACh-receptor activation on BC3H-1 cells. The channel opening rate is estimated to be about 450 s-1 and the closing rate about 35 s-1 (-70 mV, 11 degrees C). The concentration dependence of closed durations suggests that some positive co-operativity exists in agonist binding. The dissociation constant with one ACh molecule bound is about 50 microM, and that with two bound is about 10 microM (for an ACh receptor with a closed channel). 7. Saturation is not observed with carbamylcholine, even at 1 mM. The data are consistent with data obtained at low concentrations of carbamylcholine, and are in over-all agreement with the interpretation of data obtained with ACh. The affinity for carbamylcholine is estimated to be about 20-fold lower than with ACh.(ABSTRACT TRUNCATED AT 400 WORDS)